Deforestation increases the abundance of rodents and their ectoparasites in the Lacandon forest, Southern Mexico - Barriga-Carbajal, María Lourdes (2023)
Introduction: An important ecosystem service tropical forests provide is disease control. However, few studies have focused on analyzing how species more suitable to be zoonotic vectors are affected by deforestation. Objective: We evaluated how deforestation affects the abundance and species richness of rodents and their associated ectoparasites in Marques de Comillas, Chiapas, Southern Mexico. Methods: We captured rodents in 6 landscape units (LU), 1 km² each, with different percentages of tree cover (0.7, 5, 40, 46, 78, and 95 %). In each LU we set 90 Sherman traps that remained active 24 hours for 7 days during two sampling seasons in October 2019, and September 2020. All the captured rodents were checked for ectoparasites in their fur, which were collected to be identified at the lab. Results: We captured 70 rodents of five species: Sigmodon toltecus, Heteromys desmarestianus, Ototylomys phyllotis, Peromyscus mexicanus, and Oryzomys couesi. Rodent abundance increased with forest loss (R² = 0.706, P = 0.022). The greatest richness of rodent species occurred in sites with intermediate forest cover (40 % and 78 %). The most abundant species were S. toltecus (N = 45) followed by O. couesi (N = 9), these species dominated in sites with less forest cover. We recorded a total of 23 different ectoparasites, from these we identified 15 at the species level and eight at the genus level. We detected three species of ectoparasites (Amblyomma sp., Ornithonyssus bacoti, and Androlaelaps fahrenholzi) known to be vectors of zoonotic diseases. Conclusions: We found that the ongoing loss of forests promotes the proliferation of zoonotic disease vectors, which can potentially increase the frequency of affectation among the local population.